A meta-analysis of the determinants of patient satisfaction and loyalty. Issue 2 (3rd April 2022) - Olesen, Karin; Bathula, Hanoku
Abstract: In the contemporary competitive environment, healthcare providers have had to ensure that their customers are satisfied with the quality of medical service they receive as this is critical in customer retention and their repeated use of the service of the healthcare provider. Taking the patient's perspective, several studies have attempted to identify the determinants of patient satisfaction and their loyalty toward healthcare providers. Studies have yielded mixed results and to get a clearer understanding of these relationships, we perform a meta-analysis of 13 studies to test nine hypotheses. We discuss the implications of the results.